Pengaruh Media Pembelajaran Berbasis Articulate Storyline Terhadap Motivasi Belajar dan Kepuasan Belajar Pada Pembelajaran Daring - Danita Kurnia Anfira; Sri Dwiastuti; Dewi Puspita Sari (UNIVERSITAS PGRI MADIUN, 2022)
This study aims to determine the effect of Articulate Storyline-based learning media on learning motivation and satisfaction, as well as its effectiveness in online learning. The method used is Quasi-Experimental, the research design is Pretest-Posttest Nonequivalent Control Group Design. The sample was students of class XI MIPA 2 and XI MIPA 6. Collecting data through observation, interviews, documentation, questionnaires, and cognitive tests. Hypothesis testing using Manova to determine the effect, regression test to determine the extent of the effect, and N-Gain test to determine the effectiveness of the media. The results of the Manova test showed a sig=0.00 so H0 was rejected. Regression test results of learning motivation aspects: desire to achieve success (17.16%), motivation and learning needs (15%), future aspirations (15.61%), appreciation in the learning process (12.65%), activities interesting in learning (21.68%), and a conducive learning environment (17.92%). The results of the regression test for learning satisfaction aspects: tangible (29.56%), assurance (16.33%), empathy (23.68%), reliability (24.37%), and responsiveness (5.94%). The N-Gain result is 68.44%. It can be concluded that there is an effect of media on aspects of motivation and learning satisfaction, and the effectiveness is in the category of being quite effective (medium) on motivation and learning satisfaction.